Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2147/copd.s97027
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of pomegranate juice reduces emphysematous changes and injury secondary to cigarette smoke in an animal model and human alveolar cells

Abstract: BackgroundCigarette smoke (CS) increases oxidative stress (OS) in the lungs. Pomegranate juice (PJ) possesses potent antioxidant activities, attributed to its polyphenols. This study investigates the effects of PJ on the damaging effects of CS in an animal model and on cultured human alveolar cells (A549).MethodsMale C57BL/6J mice were divided into the following groups: Control, CS, CS + PJ, and PJ. Acute CS exposure was for 3 days, while chronic exposure was for 1 and 3 months (5 days of exposure/week). PJ gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…Animal models have been used to investigate the pathology of a wide range of chronic inflammatory diseases—COPD, IBD, metabolic and cardiovascular disorders, neurodegenerative diseases, RA, cancer—in which inflammation is induced experimentally by genetic manipulation or pharmacologically (diet, drugs, or exogenous toxicants) ( Table 4 ). These studies examined the effects of different pomegranate-related products, including whole fruit juice [ 19 , 21 , 26 , 41 , 42 , 43 , 48 , 50 , 60 ] or extract [ 22 , 24 , 26 , 40 , 43 , 44 , 52 , 55 , 56 , 59 , 67 , 68 , 69 ], extracts obtained using various parts of the fruit (e.g., peel [ 17 , 45 , 47 , 58 ], seeds [ 20 , 43 , 46 , 50 , 54 ], flowers [ 27 , 45 ], leaves [ 18 ]), concentrated extracts (POMx TM [ 65 ], Pomanox ® [ 51 ]) and bioactive molecules found in pomegranates (punicalagin [ 53 ], EA [ 23 , 24 , 25 , 49 , 57 ], punicic acid [ 20 ]) and their derived metabolites (urolithins […”
Section: Resultsmentioning
confidence: 99%
“…Animal models have been used to investigate the pathology of a wide range of chronic inflammatory diseases—COPD, IBD, metabolic and cardiovascular disorders, neurodegenerative diseases, RA, cancer—in which inflammation is induced experimentally by genetic manipulation or pharmacologically (diet, drugs, or exogenous toxicants) ( Table 4 ). These studies examined the effects of different pomegranate-related products, including whole fruit juice [ 19 , 21 , 26 , 41 , 42 , 43 , 48 , 50 , 60 ] or extract [ 22 , 24 , 26 , 40 , 43 , 44 , 52 , 55 , 56 , 59 , 67 , 68 , 69 ], extracts obtained using various parts of the fruit (e.g., peel [ 17 , 45 , 47 , 58 ], seeds [ 20 , 43 , 46 , 50 , 54 ], flowers [ 27 , 45 ], leaves [ 18 ]), concentrated extracts (POMx TM [ 65 ], Pomanox ® [ 51 ]) and bioactive molecules found in pomegranates (punicalagin [ 53 ], EA [ 23 , 24 , 25 , 49 , 57 ], punicic acid [ 20 ]) and their derived metabolites (urolithins […”
Section: Resultsmentioning
confidence: 99%
“…Husari et al figured out the effects of pomegranate juice (80 μmol/kg) on cigarette smoke‐induced lung damages in C57BL/6J mice. They demonstrated that pomegranate juice alleviates the expression levels of IL‐1β, IL‐6, and TNF‐α in lungs (Husari et al, ). In another study, the effects of pomegranate juice concentrate (equivalent to 80 μmol polyphenols/mL) were measured on cigarette smoking‐induced‐cardiac hypertrophy in rats.…”
Section: Resultsmentioning
confidence: 99%
“…Animals received a continuous flow of cigarette smoke or room air into the airways via the “nose only” delivery system. As described before, the smoking rate was controlled to one puff of smoke each minute (Husari et al, 2016). Rats of the CS and CS + AO groups were exposed to cigarette smoke generated from 3R4F cigarettes (University of Kentucky, Lexington, KY, USA), which are scientifically prepared cigarettes concentrated with toxins and chemical rendering the study timeline suitable to observe the effects of smoking on the rats (Roemer et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The other groups received placebo free drinking water. The dose of pomegranate juice supplementation was deduced from previous studies performed by our group (Husari et al, 2014, 2016). …”
Section: Methodsmentioning
confidence: 99%